Neuromuscular hamartoma of the sciatic nerve: Case report and review of the literature - Lam, Sandi (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Neuromuscular hamartomas are rare benign tumors with mature skeletal elements mixed with mature neural elements. They present typically as solitary lesions in childhood and have been reported to be associated with cranial nerves or large peripheral nerves such as the brachial plexus, median nerve, and sciatic nerve. To date, eight cases of sciatic nerve neuromuscular hamartomas have been reported. We present a case along with an outline for the natural history of the disease with a review of the literature of the reported cases dating back to 1895. CASE DESCRIPTION: An 11-year-old boy presented with progressive right lower extremity pain and atrophy. Magnetic resonance imaging revealed a large right sciatic nerve mass, and electromyography demonstrated evidence of ongoing denervation and reinnervation. Initial computed tomography-guided biopsy was unrevealing and subsequent open biopsy was consistent with neuromuscular choristoma. CONCLUSION: Neuromuscular choristomas represent a rare disease. Symptoms of foot deformity, leg size discrepancy, and pain merit a complete work-up including spinal and peripheral nerve etiologies.